Carney Complex with Multiple Cardiac Myxomas, Pigmented Nodular Adrenocortical Hyperplasia, Epithelioid Blue Nevus, and Multiple Calcified Lesions of the Testis: A Case Report - Kim, Hyunchul; Cho, Hyun-Yee; Lee, Jeong Nam; Park, Kook-Yang (Journal of pathology and translational medicine, 2016)
KCI Citation Count: 0